Past and projected temporal trends in arthroscopic hip surgery in England between 2002 and 2013. Issue 1 (21st March 2016) - Palmer, A J R; Malak, T T; Broomfield, J; Holton, J; Majkowski, L; Thomas, G E R; Taylor, A; Andrade, A J; Collins, G; Watson, K; Carr, A J; Glyn-Jones, S
Abstract : Introduction: Hip arthroscopy is increasingly adopted for the treatment of intra-articular and extra-articular pathologies. Studies from USA demonstrate a 365% increase in the number of procedures performed between 2004 and 2009 and 250% increase between 2007 and 2011. There is limited evidence of long-term efficacy for this procedure and hip arthroscopy is not universally funded across England. The aim of this study is to describe temporal trends in the adoption of hip arthroscopy in England between 2002 and 2013 and to forecast trends for the next 10 years. Methods: A search of the Hospital Episodes Database was performed for all codes describing arthroscopic hip procedures with patient age, sex and area of residence. Results: 11 329 hip arthroscopies were performed in National Health Service hospitals in England between 2002 and 2013. The number of hip arthroscopies performed increased by 727% (p<0.0001) during this period and is forecast to increase by 1388% in 2023. Females represent 60% of all patients undergoing hip arthroscopy (p<0.001). Median age category is 40–44 for females and 35–39 for males and average age decreased during the study period (p<0.0001). There is significant regional variation in procedure incidence. In the final year of this study the highest incidence was in the Southwest (8.63/100 000 population) and lowest in East Midlands (1.29/100 000 population). Conclusions: The increase in number of hip arthroscopies performed in England reflects trends in USA and continued increases are forecast. Evidence from robust clinical trials is required to justify the increasing number of procedures performed and regional variation suggests potential inequality in the provision of this intervention.